Navigating uncertainty: Trauma quality improvement in urban India - Berg, Johanna ; 0000-0001-7553-7337 (2025)
Background and aim Improving the quality of health care is a global priority, yet many conventional quality improvement approaches, rooted in industrial models of standardisation and control, struggle to account for the uncertainty and complexity of clinical care. Trauma, defined as external injury and the body's physiological response, causes about 4.4 million deaths each year. The impact is greatest in low- and middle-income countries, where trauma is a leading cause of quality-related deaths. Trauma care involves time pressure, interdisciplinary teams, and high variability. This thesis investigates if, and how, a trauma quality improvement programme improves patient outcomes. The work is based on four empirical studies embedded in the Trauma Audit Filter Trial, a multicentre study evaluating a programme using audit filters and multidisciplinary case reviews in urban India. Audit filters are statements of agreed standards of care; when care deviates from these, the case is selected for review. Methods and results Study I used a Delphi method to identify audit filters appropriate for the local context. Filters developed in other low- and middle-income countries were perceived as highly useful, and perceived usefulness was linked to medical relevance and feasibility. Study II, a prospective controlled interrupted time series trial, showed an 11% reduction in in-hospital mortality after programme implementation, while also highlighting confounding external factors and the limits of attributing causality in complex systems. Study III assessed the effect on health-related quality of life, showing that while survival improved, health-related quality of life slightly declined, likely because more severely injured patients survived, highlighting rehabilitation needs. Study IV used reflexive thematic analysis of interviews with participants in multidisciplinary review meetings to identify mechanisms through which the programme contributed to improvement. These included system-level awareness, shared understanding, navigation of hierarchical structures, and ethical sensitisation. Conclusion A trauma quality improvement programme based on case review and multidisciplinary discussion may reduce mortality in settings with a high burden of preventable deaths. Quality improvement in complex systems depends on structures that enable continuous learning, strengthen the forms of knowledge used in medical decision-making, and increase practitioners' understanding of the systems in which they work. Such approaches support better decision-making, enhance adaptability, and help identify and address areas for improvement within local environments. This thesis contributes to understanding how quality improvement can lead to change in trauma care and may help inform the design and implementation of similar programmes in other contexts. The knowledge gained about the mechanisms of improvement may also inform quality improvement efforts in other areas of health care.